Mï£¥etis and violence in Machiavellian political theory - Queiroz, Regina Maria da Cruz (Revista Archai, 2017)
The quest for winning and preserving political power in Machiavelli’s The Prince is led by the bellicose version of the pre-classical and mythological concept of mï£¥etis or cunning rationality. In opposition to a domestic version of cunning rationality, understood as the rationality of the weak, Machiavellian mï£¥etis is a prudential and deceptive rationality of the strong. Bellicose cunning rationality does not, however, prevent the prince from falling into the hubris of violence, and does not avoid undermining cunning rationality itself. Our article evaluates and circumscribes the contribution, as well as the theoretical and practical limits of the Machiavellian bellicose cunning rationality.